(untitled) (Educação em Revista, 2023)
Can the gestures we perform aid the teaching and learning process? The present paper summarizes the state of the art on the subject within the field of education, with a specific eye on gestural communication. Research has been found at virtually all levels of education regarding the use of gestures as a way to assist students in learning a second language, inclusive education, and science and math education. In general, there is solid evidence supporting that gestural communication helps in the evaluation and introduction of a new word in the teaching of a second language; as an additional resource for teachers and students with disabilities and as a tool to contribute to the teaching of concepts considered abstract and complex in the field of science and mathematics teaching. Of interest is the strong evidence that gesture constitutes a hidden yet powerful channel to exchange information, learn, and even as a tool to help reason.